The value of dehydrated alfalfa and delayed grain feeding young cows on winter bluestem - E.F. Smith; D. Richardson; C.L. Drake; M.C. Hall (Kansas Agricultural Experiment Station Research Reports, 1968)
Two primary objectives of this test were to: (1) compared dehydrated alfalfa with soybean oil meal as a winter supplemental feed on bluestem pasture for young cows to be bred shortly after the winter feeding period. (2) Determine any merit in feeding grain the last 50 days of the winter period compared with feeding the same total amount of grain throughout the winter when heifers are to be bred shortly after the winter feeding period.
Keywords: Cattlemen' s Day; 1968; Report of progress (Kansas State University. Agricultural Experiment Station); 518; Beef; Dehydrated alfalfa; Winter bluestem; Soybean oil meal